Internal phoshorus loading potential of a semiarid reservoir: an experimental study - Cavalcante,Hérika (2021)
Abstract: Aim To determine the internal P loading potential of semiarid tropical reservoir sediment while verifying the driving factors that affect P release rates. Methods An experiment was performed with water and sediment from the reservoir Boqueirão de Parelhas in Brazil. The effects of three variables on P release were studied: air temperature (region average of 28 °C and 32 °C, simulating an increase of 4 °C), pH (region average of pH 8, more acidic pH 6 and more alkaline pH 10) and oxygen (presence and absence). In addition, P fractionation analysis was performed on the P forms in the sediment. Results It was found that the minimum P release was in an oxic treatment at pH 6 and temperature 28 °C (0.22 mg m-2 d-1 ± 0.13) and the maximum P release in an anoxic treatment at pH 10 and temperature 32 °C (2.1 mg m-2 d-1 ± 0.15). The total P in the sediment was 597 mg kg-1, and the major P form in the sediment was NaOH-rP, the P bound to aluminum, corresponding to 42% of the total P. Conclusion These results allow us to confirm that the sediment of the Boqueirão reservoir is susceptible to the release of P bound to aluminum due to the prevalence of this form in its sediments concomitant with the high temperatures and alkaline pH of the water. This scenario can be aggravated by climate change.